The Effect of Service Quality and Facilities on Transjakarta User Intention Through Customer Satisfaction Index - Indriyati Indriyati; Nita Rosmaladewi; Euis Saribanon; Dian Anom Baskoro; Otto Sugiharto Prakoso (Dinasti International Journal of Education Management and Social Science, 2026)
This study set out to analyze the effect of service quality and facilities on TransJakarta users’ intention, with the Customer Satisfaction Index (CSI) as a mediating variable. Public transportation plays an important role in supporting urban mobility; therefore, improving service quality is considered a key factor in maintaining sustainable usage. This research adopts a quantitative approach using a survey method, distributing questionnaires to 200 TransJakarta users in the DKI Jakarta area. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS), together with an expanded evaluation of the measurement model (loadings, AVE, Composite Reliability, HTMT, SRMR, Q², f², VIF, PLSpredict) and a Common Method Bias check (Harman’s single-factor test). When estimated directly from the item-level data, the measurement model did not meet conventional convergent-validity and reliability thresholds, and none of the hypothesized structural paths (service quality and facilities on CSI; CSI on user intention) reached statistical significance once the full model was bootstrapped. Common Method Bias was ruled out as the explanation. These findings indicate that, on this dataset, the CSI-mediation model is not empirically supported, and that the survey instrument requires re-examination before the hypothesized relationships can be meaningfully tested.